TERRA beyond cancer: the biology of telomeric repeat‐containing RNAs in somatic and germ cells - Rivosecchi, Julieta; Cusanelli, Emilio (Frontiers in Aging, 2023)
The telomeric noncoding RNA TERRA is a key component of telomeres and it is widely expressed in normal as well as cancer cells. In the last 15 years, several publications have shed light on the role of TERRA in telomere homeostasis and cell survival in cancer cells. However, only few studies have investigated the regulation or the functions of TERRA in normal tissues. A better understanding of the biology of TERRA in non-cancer cells may provide unexpected insights into how these lncRNAs are transcribed and operate in cells, and their potential role in physiological processes, such as aging, age-related pathologies, inflammatory processes and human genetic diseases. In this review we aim to discuss the findings that have advanced our understanding of the biology of TERRA using non-cancer mammalian cells as a model system.